Nicaragua Diagnostic Review of Consumer Protection in Financial Services : Volume 1. Key Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
In 2010, over 92 percent of the assets in the Nicaraguan financial system were concentrated in the banking sector, while microfinance managed over 5 percent, and all the remaining segments covered less than 3 percent. Starting in the late 1990s and until 2007, the microfinance sector in Nicaragua has expanded robustly at 20 percent average annual growth rate and has been a significant factor of economic growth, particularly in the agricultural small and medium enterprise (SME) sector. The 2008 financial crisis led to a rapid deterioration of the microfinance credit portfolio and the microfinance lending contracted by nearly 20 percent in 2009. While partly this was due to spiking interest rates, over indebtedness and slowing demand, research has shown that inadequate consumer protection and low financial literacy in the microfinance sector also played a role. In order to improve Nicaraguan consumers’ confidence in their financial institutions, this World Bank’s diagnostic review presents strengthening consumer protection in five key areas. Volume I of the review summarizes the key findings and recommendations and volume II provides a detailed assessment of the Nicaraguan consumer protection institutional, legal, and regulatory framework compared to the good practices for three financial segments, namely banking, nonbank credit institutions, and insurance. Volume II also includes an annex that analyzes the results of a field research with financial consumers in Nicaragua.